2017
DOI: 10.4103/2249-4863.214433
|View full text |Cite
|
Sign up to set email alerts
|

A study of knowledge, attitude and practice regarding administration of pediatric dosage forms and allied health literacy of caregivers for children

Abstract: Context:Caregivers of sick children have to be careful with medicine dosing and giving medicines to a reluctant child can be challenging.Aim:To assess the knowledge, attitude, and practices of caregivers regarding pediatric medicine administration and health literacy allied to this task.Settings and Design:This cross-sectional study was carried out on outpatient and inpatient basis in the pediatrics department of a teaching hospital over 6 months.Subjects and Methods:Data regarding sociodemographic profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“… 3 4 The inability to administer medication correctly may result in adverse drug events and poor patient clinical outcomes. 5 Causes of medication administration problems at home are multifactorial and potentially depend on various factors. 2 So, in order to improve medication administration by parents and patients, an initial assessment of the current problems and factors that may contribute to this issue must be identified first.…”
Section: Introductionmentioning
confidence: 99%
“… 3 4 The inability to administer medication correctly may result in adverse drug events and poor patient clinical outcomes. 5 Causes of medication administration problems at home are multifactorial and potentially depend on various factors. 2 So, in order to improve medication administration by parents and patients, an initial assessment of the current problems and factors that may contribute to this issue must be identified first.…”
Section: Introductionmentioning
confidence: 99%
“…Only caregivers who are able to handle the medications correctly at home can shield their children from undesirable adverse events [5]. While dosing errors are common with liquid formulations [7,8,26], it is found that most caregivers in this study were able to perform the measurement according to the instructions.…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that health care providers have been providing them with su cient medication-related information, as highly recommended in the existing guidelines [23,24]. In contrast with caregivers from other developing countries who still tended to use a household spoon for medication administration [7,9], all participants in this study managed to measure the medication correctly by using a proper measuring device. However, unlike other countries [18,25], caregivers in Malaysia were commonly not familiarized with the generic names of medications [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations